Rancang Bangun Sistem Database Tilang Kendaraan Angkutan Umum dan Angkutan Barang Dinas Perhubungan Kota Jayapura - Fifian Theresia Sibi; Jim Lahallo (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The Jayapura City Transportation Agency faces significant challenges in managing traffic violation data due to rapid population and economic growth. The use of Excel-based systems has proven inadequate, so a more integrated and efficient information system update is needed. Thus, the research and development method to design a web-based data archiving information system application with a waterfall methodology approach. It is hoped that this application can improve the efficiency of filing and searching for violation data, as well as support better traffic control in Jayapura City.